2020
DOI: 10.4054/demres.2020.43.24
|View full text |Cite
|
Sign up to set email alerts
|

The labor force participation of Indian women before and after widowhood

Abstract: BACKGROUND Due to its young age structure and taboos on widow remarriage, India has a large and relatively young female widow population. Many of India's widows are in prime working ages. India has one of the lowest female labor force participation rates in the world. OBJECTIVE This paper calculates the effect of widowhood on the labor force participation of Indian widows. The analysis documents how labor force participation changes associated with widowhood vary by age, caste/religion, relation to head of hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Microfinancing provides women greater confidence to meet potential financial crises, without which they face challenges in obtaining a loan. 20 Importantly, this evaluation revealed that Sampan is particularly effective in its adaptiveness as well as its human-centred approach to empowering widows. Qualitative studies of widows' experiences have highlighted the loss of emotional support-defined as availability of sympathy, affection, and the option of having someone with whom to share worries.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Microfinancing provides women greater confidence to meet potential financial crises, without which they face challenges in obtaining a loan. 20 Importantly, this evaluation revealed that Sampan is particularly effective in its adaptiveness as well as its human-centred approach to empowering widows. Qualitative studies of widows' experiences have highlighted the loss of emotional support-defined as availability of sympathy, affection, and the option of having someone with whom to share worries.…”
Section: Discussionmentioning
confidence: 92%
“…Taking up formal, structured employment can be difficult for widows, due to pressures to conform to strict social seclusion after the death of their husband. 20 Sampan's livelihood programs provided widows an opportunity to engage in the local economy, primarily through sales of the produce from the seeds they were provided. This facilitated the widows forming livelihoods and developed a sense of connection and engagement with their community.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the labour participation of women is significantly affected by widowhood. [ 28 ] studies the impact of widowhood on Indian women’s labour force participation using panel data that tracks women before and after the event of widowhood. The results confirm a strong age pattern, where women widowed before the age of 52 saw an increase in the number of days worked, while women widowed after the age of 52 saw a reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our literature review indicates that selected social and economic aspects, such as the wealth and welfare of widows, have been investigated in developed countries [ 25 , 27 , 28 ]. In addition, efforts have been made to propose several solutions to mitigate poverty after widowhood [ 23 , 25 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…India has one of the lowest female labor participations in the world. Only a quarter of India's women are in the labor force (Reed 2020) with variations according to regional states, religion, caste, social class, and other intersecting factors. Marriage and familial practices are seen as major reasons for this abysmal situation.…”
mentioning
confidence: 99%